Expert MySQL - Bell, Charles A. 1962- (The expert's voice in databases, 2012)
Expert MySQL is the leading reference for learning, understanding, and extending the MySQL server. It unlocks the full promise of open source by showing how to modify the code, create your own storage engine, build your own authentication plugins, and even add your own functions and commands to the SQL language. No other book provides the level of detail or the extensive examples of the inner workings of MySQL that have taken engineers years to master. Expert MySQL is a must have book for all systems integrators, engineers, and software developers working with the MySQL server code. Expert MySQL is also a wealth of information on key aspects of MySQL internals. You'll learn about internal query representation, how the optimizer creates execution plans, and how to exert control over those plans for optimal performance in your environment. You'll even learn to build your own query optimizer, giving insight that can help you understand and resolve tough performance problems. High-availability and replication are also covered, making Expert MySQL a must-have book for anyone doing high-end work involving MySQL. Shows how to customize MySQL and its storage and authentication engines Provides in-depth knowledge of internals for use in query tuning and performance troubleshooting Covers high-end features such as high-availability and replication.